Unveiling the physicochemical properties and chemical profile of artisanal jabuticaba wines by bromatological and NMR-based metabolomics approaches. (July 2021) - Macedo, Ellis Helena B.C.; Santos, Gilson C.; Santana, Michele N.; Jesus, Edgar Francisco O.; de Araújo, Ubiratan B.; Anjos, Marcelino J.; Pinheiro, Anderson S.; Carneiro, Carla S.; Rodrigues, Igor A.
Abstract: The jabuticaba fermented beverage, or jabuticaba wine, shows certain sensorial properties similar to those of red wine. Here, a comprehensive bromatological analysis of seven artisanal jabuticaba wines (JW1-7) revealed different physicochemical and color properties. Among the samples, JW6 stood out for having the highest content of monomeric anthocyanins (28.8 mg/L) and minerals, such as K (1594.58 μg/mL) and P (49.89 μg/mL). Surprisingly, the Cu content found in all samples exceeded the maximum limit established for this metal in wines. Using NMR-based metabolomics, more than 100 compounds were identified, most of them were carbohydrates. Furthermore, a discriminant analysis of the metabolomic data by PCA revealed that the contents of sucrose, glucose, stachyose and quinic acid enabled the differentiation of the wines and wine producers. The results presented here pave the way for further investigations into the composition of jabuticaba wines and their impact on product quality. Highlights: Jabuticaba wines show high acidity and low content of monomeric anthocyanins . K, Ca and P are the main minerals in artisanal jabuticaba wines. Spectral measurements showed low values of anthocyanin-related color. More than 100 metabolites were identified by NMR-based metabolomics . The contents of carbohydrates and quinic acid discriminate the different wines.